New York Paper - Note on the Use of Crude Petroleum as Fuel for Raising Steam at the South Chicago Works - E. C. Potter (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1889)
FUEL-OIL was first substituted for coal at these works in September, 1888. It was first applied in the converting-department to the battery of boilers, consisting of 14 tubular boilers, 16 feet in length by 5 feet in diameter. To operate these boilers with coal for 24 hours required 14 strikers, 3 ash-wheelers, 6 men unloading coal, and 2 water-tenders, making a total of 25 men. With fuel-oil the same boilers require for the same period 2 water-tenders and 4 men to attend to the burners, making a total of 6 men. This gives a saving of 19 men, which, at an average of $2 per day each, amounts to $38 per day. Comparing the consumption of oil with that of coal, we find that for the week ending January 5, 1889, with an ingot output of 6403 tons, 2731 barrels of fuel-oil were used as against a necessary consumption of coal for the same work of 848 tons, showing 3.22 barrels of fuel-oil to be equivalent to one ton of Indiana block-coal. Figuring oil at 60 cents per barrel, and coal at $2.15 per ton, we have as the cost of oil $1.93, as against $2.15 for its equivalent in coal. In December, 1888, the rail-mill battery of 26 boilers, of the same dimensions as those in the converting-department, was equipped for fuel-oil. For the week ending January 5, 1889, with a rail out-put of 5208 tons, 5987 barrels of oil were consumed, as against a necessary consumption of coal, to do the same work, of 1805 tons, showing 3.31 barrels of fuel-oil to be equivalent to one ton of Indiana block-coal, which at the costs named above would show $1.98 worth of fuel-oil to he equal to $2.15 worth of coal. The labor required to operate the rail-mill boilers for 24 hours, with coal as fuel,is: 26 stokers, 4 water-tenders, 6 ash-wheelers, 12 men unloading coal; total, 48 men. With oil as fuel, the same work requires 4 water-tenders and 6 men to attend to the burners; total, 10 men; a saving over coal of 38 men in 24 hours, which, at an average price of $2 per day, would be $76 per day. In the brief experience we have had with oil as fuel, we find that the efficiency of the boilers is somewhat increased and the repairs are